Moving tree to Logan Circle (Philadelphia Evening Bulletin, 1936)
"Workmen replanting a paulownia empress tree in Logan Circle on the Parkway. Weighing eight tongs, it was moved from the Greenland Nursery in Fairmount Park." With clipping